2012
DOI: 10.1021/jf3007213
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Isolated Cranberry (Vaccinium macrocarpon Ait.) Proanthocyanidins to Catechin and Procyanidins A2 and B2 for Use as Standards in the 4-(Dimethylamino)cinnamaldehyde Assay

Abstract: The 4-(dimethylamino)cinnamaldehyde (DMAC) assay is currently used to quantify proanthocyanidin (PAC) content in cranberry products. However, this method suffers from issues of accuracy and precision in the analysis and comparison of PAC levels across a broad range of cranberry products. Current use of procyanidin A2 as a standard leads to an underestimation of PACs content in certain cranberry products, especially those containing higher molecular weight PACs. To begin to address the issue of accuracy, a meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(116 citation statements)
references
References 43 publications
5
111
0
Order By: Relevance
“…Here, the levels of total extractable proanthocyanidins were measured in the seed coat of both cranberry bean RILs as a function of seed development. This assessment was based on a simple spectrophotometric assay following the incubation of seed coat extracts with acidified DMACA to yield a chromophore having a maximum absorbance at 640 nm [43, 44]. Total extractable proanthocyanidin levels in cranberry bean seed coats were quantified by comparison to a known range of authentic procyanidin A2 dimer standard [41].…”
Section: Resultsmentioning
confidence: 99%
“…Here, the levels of total extractable proanthocyanidins were measured in the seed coat of both cranberry bean RILs as a function of seed development. This assessment was based on a simple spectrophotometric assay following the incubation of seed coat extracts with acidified DMACA to yield a chromophore having a maximum absorbance at 640 nm [43, 44]. Total extractable proanthocyanidin levels in cranberry bean seed coats were quantified by comparison to a known range of authentic procyanidin A2 dimer standard [41].…”
Section: Resultsmentioning
confidence: 99%
“…1). Our previous work using MALDI TOF MS in linear mode detected c-PAC with a DP of up to 26 and chromatographic data suggested that c-PAC did not contain other classes of flavonoids (Feliciano et al, 2012). The observed m/z values were within ±0.5 amu of predicted m/z based on the equation m/z = 290 + 288dÀ2A + c, where 290 represents the molecular weight of the terminal catechin/epicatechin unit, d is the degree of polymerization, A is the number of A-type interflavan bonds and c is the molecular weight of sodium or potassium cations (Supplementary Information- Table 1).…”
Section: Qualitative Analysis Of C-pacmentioning
confidence: 89%
“…However, we did not estimate range in DP in this research because reflectron mode MALDI-TOF MS did not detect oligomers above undecamers with a S/N greater than 3. Linear mode MALDI-TOF MS is capable of detecting oligomers with a DP of up to 26 flavan units in cranberry PAC (Feliciano et al, 2012), but does not have sufficient baseline resolution to adequately deconvolute isotope patterns. The use of reflectron mode MALDI-TOF MS as described in this paper gave baseline resolution of 1 amu for oligomers up to the undecamers and therefore we were able to determine ratios of interflavan bonds for oligomers with DP from 2 to 11.…”
Section: Discussionmentioning
confidence: 99%
“…Here we used the OS4-dimethylaminocinnamaldehyde (DMAC) method rather than the often used BL DMAC method. The latter overestimates (poly)phenol levels due to the use of procyanidin A2 as a standard instead of a better representation of cranberry proanthocyanidin complexity; OS DMAC includes a standardized extract comprehending larger polymers [29]. Therefore, using what we believe is a more appropriate method of quantification of (poly)phenols in cranberry juice may explain the low urinary recovery.…”
Section: Discussionmentioning
confidence: 99%